2017
DOI: 10.1016/j.labeco.2017.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Racial discrimination in the U.S. labor market: Employment and wage differentials by skill

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 44 publications
(61 reference statements)
0
11
0
Order By: Relevance
“…Sociologically, as Roediger (2007) argues, labor structures can rearrange racial stratification: The possibility of increased White labor in the service sectors is thus a potential force for reinvigorating racial inequality. For instance, in competition for the same low-wage service jobs, Black and Hispanic workers may be pushed out due to other structural disadvantages like lower labor market power (Borowczyk-Martins, Bradley, & Tarasonis, 2017) . Despite White workers being much more affected by occupational automatability in the aggregate, the difficulty of adjusting within the labor market may be much more difficult for non-White workers.…”
Section: Resultsmentioning
confidence: 99%
“…Sociologically, as Roediger (2007) argues, labor structures can rearrange racial stratification: The possibility of increased White labor in the service sectors is thus a potential force for reinvigorating racial inequality. For instance, in competition for the same low-wage service jobs, Black and Hispanic workers may be pushed out due to other structural disadvantages like lower labor market power (Borowczyk-Martins, Bradley, & Tarasonis, 2017) . Despite White workers being much more affected by occupational automatability in the aggregate, the difficulty of adjusting within the labor market may be much more difficult for non-White workers.…”
Section: Resultsmentioning
confidence: 99%
“…It is also possible that adverse selection is relevant to the observed differences in full-time employment. Some individuals may not perceive full-time labor market opportunities for which they are eligible (as a result of limited human capital acquisition, a criminal record, compromised individual functioning, and/or discrimination based on race/ethnicity; Borowczyk- Martins et al, 2017) as lucrative enough to seek out employment (i.e., full-time employment in the secondary labor market that is arduous in task, offers few benefits, pays minimum wage, and/or stressinducing). Unfortunately, it is not possible to speak to these possible mechanisms due to the small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…The influence between wages and employment can be realized as long as regulation, job security, and aggregate demand for labor can take place positively. Whereas optimal wages and remuneration factors provide a real impact that bridges between wages and positive employment (Baek & Park, 2016;Vazzana & Bachmann, 1995;Clemens & Wither, 2019;Caliendo et al, 2018;Bauducco & Janiak, 2018), the factor of discrimination in terms of wages will harm employment (Borowczyk-Martins et al, 2017;Cheng et al, 2013;Perugini & Pompei, 2016;Wang et al, 2019). Conversely, other studies (e.g., Lee & Wolpin, 2010;Säve-Söderbergh, 2019;Schober & Winter-Ebmer, 2011;Xu et al, 2015) found that differences between wages by gender did not affect employment.…”
Section: Literature Review and Hypothesesmentioning
confidence: 95%